Do the elderly and those with comorbid chronic physical conditions have improved access to outpatient psychotherapy post structural reforms in Germany? Results of the ES-RiP study - Jedamzik, Johanna; Kampling, Hanna; Christoffer, Andrea; Szardenings, Carsten; Heuft, Gereon; Friederich, Hans-Christoph; Kruse, Johannes (Frontiers in Psychiatry, 2024)
Background In 2017, a reform of the German outpatient psychotherapy guideline was carried out, aiming to reduce waiting times and facilitate low-threshold access. This study analyzes the extent to which the implementation of the two new service elements ‘psychotherapeutic consultation times’ and ‘acute short-term psychotherapeutic interventions’ improved psychotherapeutic care for patients with mental disorders and chronic physical conditions (cMPs), for patients with mental disorders without chronic physical conditions (MnoP), and elderly patients. Methods In a quantitative secondary analysis, we analyzed health insurance data of patients with psychotherapy billing codes obtained from the National Association of Statutory Health Insurance Physicians (KBV) for the years 2015-2019, evaluating descriptive statistical parameters for specific patient groups and care services. Results Between 2015 and 2019, the number of mentally ill receiving psychotherapy at least once in the corresponding year increased by 30.7%. Among these, the proportion of cMPs-patients increased from 26.8% to 28.2% (+1.4%), while that of MnoP-patients decreased from 68.3% to 66.4% (-1.9%). The number of elderly people receiving treatment also increased. Conclusion Since increases and decreases in the percentage shares occur evenly over the years investigated, it is questionable whether the reform in 2017 has had a direct influence on these changes. Study registration ID DRKS00020344, URL: https://www.bfarm.de/DE/Das-BfArM/Aufgaben/Deutsches-Register-Klinischer-Studien/_node.html.